Rancang Bangun Fingerprint Absensi Guru Disekolah Balitaku Khatam Qur’an Berbasis Arduino - Ramadani Barus, Cici; Hermansyah (CV. Hawari, 2023)
the attendance list also includes data collection which must be recapitulated every day against the admin of my toddler khatam quran school. The attendance system can read every finger identity that is registered for all teachers at my toddler Khatam Koran school easily and does not read for fingerprints that have not been registered before.The display for the LCD is the name of each teacher and written attendance is stored if the fingerprint is registered, if the fingerprint is not registered then the display on the LCD displays an unknown fingerprint